Student Workload and Degree Profiles: the experience of CLAR credit in Latin America - Francisco Alarcón; Pablo Beneitone; Roberto de Armas; Sérgio Kieling Franco; Letícia Suñé; Diana Veneros (Universidad de Deusto, 2014)
There is growing consensus in Latin America on the necessity to reorganize the degree profiles in a competence-based and student-centred system, with identified learning outcomes, innovative learning and teaching strategies, and new methodologies for assessing competences which could be useful for students. There is also agreement on the need to build up a solid Latin America Higher Education Area -based on common benchmarks-among which a shared regional academic credit system is highly relevant. Not all Latin American higher education institutions are familiar with an academic credit system. In the countries where academic credits do exist they are generally based on traditional views which focus on teaching and transmission, rest on different concepts and definitions and consider diverse scopes for their application. With few exceptions, these countries do not use a credit system as a unit of measure of student workload to achieve learning outcomes and competences. This paper sheds light on a proposal for a common academic credit system for Latin America (CLAR) which comes out of one of the many nuances of Tuning discussion and is referred to the expected outcome 6: "Political-and educational orientations for the establishment of a system of academic credits for Latin America" (Proyecto Alfa Tuning América Latina: Innovación Educativa y Social, 2011-2013). The new credit system that this paper advocates for Latin America is based on the principle that 60 credits measure the workload of a full-time student during one academic year. As such, a CLAR credit is conceived as a unit of value that estimates the student workload, measured in hours, which he/she typically requires to achieve learning outcomes and pass a course or a semester. In order to calculate the value of CLAR credit two elements are considered: the duration of the academic year and the annual student workload. To estimate the annual student workload, a specific survey was applied in 18 countries, 189 universities and 15 subject areas. This paper shows the major results that were brought out by 10,086 questionnaires, which were responded to by students and university professors. As a result of this survey, the student workload of a full-time study programme in Latin America amounts to around 1,440 to 1,980 hours per year and in those cases one credit stands for around 24 to 33 working hours.